Comparative effectiveness of video and booklet-based range of motion education on stroke family knowledge: Quasi-experimental pretest-posttest study - Fitri Anita; Budi Antoro; Sandra Andini; Rictha Puspita Haryanti; Tubagus Erwin (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Stroke remains a leading cause of long-term disability, often resulting in impaired mobility and dependence on family caregivers. Range of Motion (ROM) exercises are essential in preventing complications and improving functional recovery among stroke patients. However, inadequate caregiver knowledge may limit optimal implementation. Educational strategies using different media, such as video and a booklet, may enhance understanding. This study aimed to compare the effectiveness of video-based and booklet-based ROM education in improving family knowledge of stroke care. Research Methodology: A quasi-experimental study with a pretest–posttest two-group design was conducted among 30 family caregivers of stroke patients (15 in the video group and 15 in the booklet group). Participants were recruited purposively from two hospitals. Knowledge was measured using a structured questionnaire administered before and after the intervention. Within-group differences were analyzed using the Wilcoxon signed-rank test, while between-group differences were assessed using the Mann–Whitney U test. Statistical significance was set at p < 0.05. Results: Both intervention groups demonstrated significant improvements in knowledge following education. In the video group, median knowledge scores increased from 9.00 to 14.00 (p = 0.001), while in the booklet group, scores increased from 10.00 to 13.00 (p = 0.003). However, no statistically significant difference was observed between groups after the intervention (p = 0.065; Mann–Whitney U test). The findings indicate comparable effectiveness between video and booklet educational media. Conclusion: Both video-based and booklet-based educational interventions effectively improve family knowledge regarding ROM exercises in stroke care. Given the absence of significant differences, the selection of educational media may be tailored to resource availability, user preference, and clinical context. Integrating both media may further optimize caregiver education and support home-based stroke rehabilitation.